Electrodiagnostic evaluation of autonomic dysfunction in patients with multiple sclerosis - Albaiaty, Mays; Farqad B. Hamdan; Anmar O. Hatem (Karbala Journal of Medicine, 2024)
Abstract Background: Autonomic dysfunction frequently affects multiple organs and systems in people with multiple sclerosis (PwMS), including the heart, bladder, and bowels, as well as sudomotor and sexual functions, and can have a significant negative impact on the quality of life. Aim: to assess the effect of MS on autonomic nervous system (ANS) functions by electrodiagnostic measures and investigate the relationship of these measures with different demographic and clinical factors such as age, sex, duration of disease, type of treatment, the Expanded Disability Severity Scale (EDSS) score, and the Composite Autonomic Symptom Score-31 (COMPASS-31) score. Methods: forty patients with a definite diagnosis of relapsing-remitting MS and 35 age- and sex-matched controls. The EDSS to assess disease severity and the COMPASS-31 questionnaire to test for degree of clinical autonomic disability, Ewing’s cardiovascular autonomic tests, and sympathetic skin response (SSR) as electrophysiologic tests for autonomic dysfunction were done. Results: The heart rate during normal (HRNB), HR response to deep breathing (HRDB), and systolic blood pressure (BP) drop from supine to standing position were significantly different in the PwMS relative to the controls. Moreover, PwMS exhibited prolonged palmar SSR latency and reduced plantar SSR amplitude. Disease duration was negatively correlated with HRNB, HRDB, and heart rate during the Valsalva manoeuvre (HTVals). EDSS is also negatively correlated with HRNB and HRDB. Furthermore, COMPASS-31 also shows a negative correlation with HRDB. On the contrary, systolic PB drop and planter SSR amplitude were positively correlated with EDSS. Conclusion: In MS, cardiac autonomic dysfunction affects both the parasympathetic and sympathetic NS. Alongside the cardiovascular system, the sympathetic sudomotor system is also impacted. The length and severity of the disease were correlated by parasympathetic abnormalities. No correlation was observed within the patient group between any autonomic function tests and age, sex, treatment type, or family history of MS. Keywords: Multiple sclerosis, EDSS, autonomic function tests, COMPASS-31